DIGITAL MARKETING ADOPTION AND CONTINUANCE CHALLENGES IN MALAYSIAN MSMES: A SYSTEMATIC REVIEW - Osman, Nurezali; Basiruddin, Rohaida; Ibrahim, Ida Shafira Anoar (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This systematic literature review synthesises Malaysian empirical evidence on the challenges that constrain the adoption and post-adoption continuance of digital marketing among MSMEs, with implications for sustained use support. Following PRISMA 2020, Databases (Scopus and Web of Science) were searched for peer-reviewed English-language studies (2015–2025). After deduplication and screening, 22 studies were included from 107 records (71 unique). A six-item quality checklist was applied. A total of 156 challenge statements were extracted and coded via thematic synthesis. Next, they were classified by phase as adoption, continuance or cross-cutting when phase indicators were unclear. Six themes emerged. Adoption constraints were dominated by capability and readiness gaps and ecosystem/infrastructure bottlenecks, pointing to skills deficits, platform complexity and uneven enabling conditions. Continuance-related challenges were less frequently reported but clustered around resource scarcity and opportunity costs, trust/risk, reputational exposure and market volatility, suggesting that sustained use declines when effort, perceived risk and uncertain returns outweigh perceived benefits. Over half of the challenges were cross-cutting, indicating limited phase specificity in the Malaysian corpus and limiting insights into discontinuance mechanisms. Future research should operationalise phase-specific constructs and use longitudinal or process-sensitive designs. Practically, programmes should complement training with maintenance support such as routines, feedback loops and risk-mitigation practices to reduce the effort–return burden of sustained digital marketing use.